The Leadership Role of The School Principal in Developing School Culture - Fadila, Tiara Nur; Ayumi, Nadia Meidina; Damanik, Yana Tasya; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
This research aims to explore the leadership role of school principals in developing school culture as well as inhibiting and supporting factors in efforts to achieve effective schools. This research is qualitative research with a literature approach. Data was collected from various relevant journals. The research data that has been collected, analyzed through text study using content analysis techniques. The research results show that the principal's leadership has an important role in developing school culture. Some of the principal's leadership roles include; The principal's role as a person, educator, manager, administrator, supervisor, leader, creator of a conducive work climate, innovator and motivator. Apart from that, there are supporting and inhibiting factors in developing school culture. Supporting factors consist of a clear school vision and mission; Harmonious relations between school members; School curriculum; An active, conducive and enjoyable learning process really supports cultural development. Inhibiting factors consist of the negative personality of teachers and students; Lack of Funding Sources; Lack of Learning Facilities and Infrastructure; Lack of habit of caring about cleanliness and loving one's health. The conclusion of this research emphasizes the important role of school principals in developing school culture, and suggests school principals strive to reduce inhibiting factors and increase supporting factors in developing school culture.